Effect of Zirconium on the Structure and Congruent Crystallization of a Supercooled Calcium Aluminosilicate Melt. Issue 6 (12th March 2015) - Strukelj, Eozen; Comte, Monique; Roskosz, Mathieu; Richet, Pascal; Pinckney, L.
<x xml:space="preserve">Abstract</x> The influence of zirconium as a nucleating agent on the congruent crystallization and relevant physical properties of a supercooled calcium aluminosilicate melt of a composition close to CaAl2SiO6 has been investigated up to 6 mol% ZrO2. Zirconium marginally affects rheological and structural properties, decreasing the viscosity of the Zr‐free melt by no more than 0.25 log unit and, as observed by Raman spectroscopy, not changing significantly the polymerization state of the material. Whereas the Zr‐free melt crystallizes congruently and heterogeneously from the sample surface to yield yoshiokaite, a stuffed derivative of the nepheline structure, addition of zirconia promotes instead bulk crystallization of tetragonal ZrO2 and then of yoshiokaite. The latter process takes place in two stages: dissolved Zr first promotes homogeneous precipitation of zirconia before yoshiokaite crystallizes congruently from a Zr‐depleted volume of melt around zirconia precipitates. This process makes zirconium, and probably other poorly soluble oxides, valuable to control congruent crystallization in silicate glass‐ceramics. From the recorded thermograms, an enthalpy of crystallization of 40 and 46 kJ/mol has been determined at 1060 and 1140 K, respectively, for CaAl2SiO6 yoshiokaite, a very low value that is likely due to the extensive atomic disorder of crystals precipitating at high degrees of supercooling.